Antimony nitrogen carbon nanosheet and its preparation method and application
Synthesis of antimony nitrogen carbon nanosheets by a one-step solvothermal method solves the problems of complex operation, high equipment requirements and low yield in the prior art, and achieves high-quality, high-yield and low-cost antimony nanosheet materials, with excellent electrochemical properties, and is suitable for potassium ion battery negative electrode materials.
Patent Information
- Application Number
- CN202310356959.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-06
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2043-04-06
AI Technical Summary
The existing preparation methods based on antimony nanosheet materials have problems such as complex operation, high equipment requirements and low yield, and it is difficult to meet the high quality, high yield and low cost requirements of potassium ion battery negative electrode materials.
Antimony nitrogen carbon nanosheets were synthesized by a one-step solvothermal method using furfural, antimony nitrogen carbon nanosheets, and carbonization treatment was used to obtain antimony nitrogen carbon nanosheet materials. This method is simple and easy to use, has low equipment requirements and high yield.
The prepared antimony nitrogen carbon nanosheet material has excellent electrochemical properties, with a specific capacity of up to 547.3mAh/g for the first charge, and the capacity retention rate can reach 92.2% after 200 cycles. It is suitable for potassium ion battery negative electrode materials.
Smart Images

Figure CN116534811B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to an antimony nitrogen carbon nanosheet and a preparation method and application thereof, belonging to the technical field related to new energy. Background Art
[0002] Due to the shortage of lithium resources, potassium-ion batteries (PIBs) have attracted much attention as a cost-effective option. This poses a major challenge to the development of high-performance electrode materials. Among the many negative electrode materials for potassium ion batteries, antimony (Sb) alloy negative electrode forms K3Sb after full discharge, which has a high theoretical specific capacity of 660mAh / g and has great application potential. However, it is also important to note that the huge volume expansion (~400%) of antimony during charging and discharging causes the active material to collapse and pulverize, lose electrical contact with the current collector, and cause rapid capacity decay and failure.
[0003] The unique morphology of (2D) antimony material gives it a very high specific surface area. When used as an electrode material, the active material is in full contact with the electrolyte, and the ion transmission path is short, which is conducive to alleviating the negative impact of volume expansion. In the preparation method of (2D) antimony material, mechanical stripping, liquid phase stripping and epitaxial growth have been proven to be successful and feasible, but the development of high-quality, high-yield, low-cost strategies is still challenging, and there is relatively little research in this field. Patent CN113059174B discloses a method for preparing metal antimony sheets by electrospinning technology, but this method has high requirements for equipment and operation, and how to further improve the electrochemical properties of metal antimony sheets is also a problem to be solved in this field. Therefore, it is very meaningful to provide a material with electrochemical properties based on antimony nanosheets for the study of potassium ion storage. Summary of the invention
[0004] In order to solve the problems of complex operation, high equipment requirements and low yield in the existing method for preparing antimony nanosheet materials, the present invention provides an antimony nitrogen carbon nanosheet and a preparation method and application thereof.
[0005] The technical solution of the present invention:
[0006] One of the purposes of the present invention is to provide a method for preparing antimony nitrogen carbon nanosheets, the method comprising the following steps:
[0007] S1, dissolving furfural and antimony trichloride in N,N-dimethylformamide solvent, and stirring to obtain a reaction solution;
[0008] S2, transferring the reaction solution to a reaction vessel for solvothermal reaction, and washing, centrifuging, and drying the product after the reaction to obtain a precursor;
[0009] S3, placing the precursor in a tube furnace for carbonization treatment to obtain antimony nitrogen carbon nanosheets.
[0010] It is further defined that the mass ratio of furfural to antimony trichloride in S1 is 2:(1-2).
[0011] It is further defined that the mass ratio of furfural to antimony trichloride in S1 is 2:1.17.
[0012] It is further defined that the solvent thermal reaction temperature in S2 is 160-180°C, the time is 8-10 hours, and the heating and cooling time is 2-3 hours.
[0013] It is further defined that the solvent thermal reaction temperature in S2 is 160°C, the time is 10 h, and the heating and cooling time is 3 h.
[0014] It is further defined that the washing in S2 is three times of washing with water and three times of washing with anhydrous ethanol.
[0015] It is further defined that the centrifugal speed in S2 is 6000-9000 rpm, and the time is 1-5 min.
[0016] It is further defined that the drying temperature in S2 is 60-80°C.
[0017] It is further defined that the thickness of the precursor obtained in S2 is 3 to 4 nm.
[0018] It is further defined that the carbonization temperature in S3 is 350-400°C, the time is 1-2h, and the heating rate is 1°C / min.
[0019] It is further defined that the carbonization temperature in S3 is 350°C, the time is 2h, and the heating rate is 1°C / min.
[0020] The second object of the present invention is to provide an antimony nitrogen carbon nanosheet prepared by the above method, and specifically the antimony nitrogen carbon nanosheet is used as a negative electrode material in a potassium ion battery.
[0021] The third object of the present invention is to provide an antimony nitrogen carbon nanosheet negative electrode material prepared by the above method, which has an initial charge capacity of 547.3 mAh / g at a current of 0.1C in a voltage range of 0.01 to 2.0 V, an output capacity of 504.5 mAh / g after 200 cycles, a capacity retention rate of up to 92.2%, and a high potassium storage capacity.
[0022] The present invention uses furfural, antimony trichloride and N,N-dimethylformamide as raw materials, synthesizes antimony nitrogen carbon nanosheets through a one-step hydrothermal method, and the potassium ion battery device using the antimony nitrogen carbon nanosheets as the negative electrode material has a higher specific capacity and cycle stability. Compared with the prior art, the present application also has the following beneficial effects:
[0023] (1) The present invention utilizes carbon monoxide produced by the decomposition of N,N-dimethylformamide to in-situ reduce trivalent antimony ions to elemental antimony, and utilizes the introduction of furfural to selectively induce the growth direction of the composite material. At the same time, the nitrogen-doped carbon coating layer buffers the volume expansion and improves the electrical conductivity and ion diffusion rate of the material, thereby obtaining an antimony nitrogen carbon nanosheet material with excellent electrochemical performance potential.
[0024] (2) The antimony nitrogen carbon nanosheet material provided by the present invention has good electrochemical potassium storage performance. In the voltage range of 0.01 to 2.0 V, the first charging specific capacity at 0.1C current is 547.3 mAh / g, and the output specific capacity after 200 cycles is 504.5 mAh / g. The capacity retention rate can reach 92.2%. It has a high potassium storage capacity and can be widely used in potassium ion battery negative electrode materials.
[0025] (3) The preparation method provided by the present invention is simple and easy to implement, has low equipment requirements and high yield, is conducive to large-scale production, and has the potential to be widely used in potassium ion battery negative electrode materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 is the X-ray diffraction spectrum of the Sb / NC composite material prepared in Example 1;
[0027] Figure 2 This is a scanning electron microscope photograph of the Sb / NC composite material precursor prepared in Example 1;
[0028] Figure 3 This is a scanning electron microscope photograph of the Sb / NC composite material prepared in Example 1;
[0029] Figure 4 This is a transmission electron microscope photo of the Sb / NC composite material prepared in Example 1;
[0030] Figure 5 This is an atomic force microscope image of the Sb / NC composite material prepared in Example 1;
[0031] Figure 6 Schematic diagram of preparing Sb / NC composite material in Example 1;
[0032] Figure 7 The charge and discharge platform curve of the potassium half-cell in the voltage range of 0.01 to 2.0 V using the Sb / NC composite material prepared in Example 1 as the negative electrode;
[0033] Figure 8A comparison chart of the cycle stability test of a potassium half-cell using the Sb / NC composite material prepared in Example 1 and commercial antimony powder as the negative electrode in the voltage range of 0.01 to 2.0 V and the current density of 100 mA / g;
[0034] Fig. 9 The rate performance test diagram of the potassium half-cell in the voltage range of 0.01 to 2.0 V using the Sb / NC composite material and commercial antimony powder prepared in Example 1 as the negative electrode respectively;
[0035] Fig.10 In order to prepare the Sb / NC composite material as the negative electrode and K 0.69 Electrochemical performance diagram of the full battery matched with CrO2 positive electrode material in the voltage range of 1.5~3.8V and current density of 5mA / g. DETAILED DESCRIPTION
[0036] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0037] The experimental methods used in the following examples are conventional methods unless otherwise specified. The materials, reagents, methods and instruments used are conventional materials, reagents, methods and instruments in the art unless otherwise specified, and can be obtained by those skilled in the art through commercial channels. Among them, the particle size of commercial antimony powder is 18um.
[0038] Embodiment 1:
[0039] like Figure 6 As shown, the specific process of preparing antimony nitrogen carbon nanosheets in this embodiment is carried out according to the following steps:
[0040] Step 1: Dissolve 2 g furfural and 1.17 g antimony trichloride in 45 ml N,N-dimethylformamide solvent, and stir magnetically for 2 h to obtain a mixed solution;
[0041] Step 2: Transfer the mixed solution obtained in step 1 to a Teflon autoclave, place it in a blast oven for solvent thermal reaction at 160°C for 10 hours, and the heating and cooling time is 3 hours. The product is washed (three times with water and three times with anhydrous ethanol), centrifuged (speed of 8000rpm, time of 3min), and dried (dried overnight at 60-80°C in a blast oven) to obtain an antimony nitrogen carbon nanosheet material precursor, abbreviated as Sb / NC composite material precursor;
[0042] Step 3: The Sb / NC composite material precursor obtained in step 2 is placed in a tubular furnace for heat treatment and carbonization at 350°C for 2 hours at a heating rate of 1°C / min to obtain an antimony nitrogen carbon nanosheet material, abbreviated as Sb / NC composite material.
[0043] Effect example 1:
[0044] The microstructure and morphology of the Sb / NC composite material and the Sb / NC composite material precursor prepared in this embodiment were characterized as follows:
[0045] (1) The X-ray diffraction spectrum of the Sb / NC composite material prepared in this example is as follows Figure 1 As shown by Figure 1 It can be seen that all characteristic peaks correspond to the characteristic peaks of elemental Sb, and no impurity peaks exist.
[0046] (2) The scanning electron microscopy images of the Sb / NC composite material precursor and the Sb / NC composite material prepared in this example are shown in FIG. Figure 2 and Figure 3 As shown in the figure, it can be seen that both the Sb / NC composite material precursor and the Sb / NC composite material have nanosheet morphology.
[0047] (3) The transmission electron scanning microscopy image of the Sb / NC composite material prepared in this example is as follows Figure 4 As shown by Figure 4 It can be seen that the outer periphery of the flake material is covered with an ultra-thin carbon layer, and the lattice spacing is 0.214nm, which belongs to the (110) crystal plane of elemental antimony.
[0048] (4) The atomic force microscopy image of the Sb / NC composite material prepared in this example is as follows Figure 5 As shown by Figure 5 It can be seen that the thickness of the nanosheets of the Sb / NC composite material is 3 to 4 nm.
[0049] Effect Example 2:
[0050] The electrochemical properties of the Sb / NC composite material prepared in Example 1 were tested as follows:
[0051] (1) The negative electrode active material (Sb / NC composite material), acetylene black and CMC were weighed in a mass ratio of 7:2:1, placed in an agate mortar and mixed in a water solvent, ground for 30 minutes, coated on a copper foil, dried in a 60°C oven, rolled and cut into pieces, and then thoroughly dried in a vacuum oven to obtain a Sb / NC composite electrode sheet. The counter electrode was a metal potassium sheet, the diaphragm was a glass fiber, the electrolyte was 5 mol / L KFSI dissolved in a DME solvent, and the battery was a 2025 button cell. The potassium storage performance was tested in the voltage range of 0.01 to 2 V.
[0052] The charge and discharge curves of the half-cell prepared with Sb / NC composite material as the negative electrode material at a current density of 100 mA / g are shown in Figure 7 As shown: In the voltage range of 0.01 to 2.0 V, the experimental group has a first-cycle coulombic efficiency of 67.4%, and a capacity retention rate of up to 92.2% after 200 cycles, showing excellent electrochemical stability.
[0053] (2) The Sb / NC composite material prepared in Example 1 was used as the experimental group, and the commercial antimony powder was used as the control group. The charge and discharge cycle performance of the Sb / NC composite material prepared in Example 1 was tested (the half-cell preparation method used in the test was as described in (1) of this effect example). The comparison results are shown in FIG. Figure 8 As shown by Figure 8 It can be seen that at a current density of 100 mA / g, the material prepared in Example 1 has the highest reversible capacity of 547.3 mAh / g after 200 cycles, while the commercial antimony powder material decays quickly. Fig. 9 The rate performance of Sb / NC composites and commercial antimony powder was demonstrated. At a high current density of 4000mA / g, the Sb / NC composite material can output a specific capacity of 105mAh / g, while commercial antimony powder has almost no capacity. This fully proves that the antimony nitrogen carbon nanosheet material obtained by this method has excellent electrochemical performance and is more advantageous for commercial promotion.
[0054] Effect Example 3:
[0055] The Sb / NC composite material prepared in Example 1 was matched with the K0.69CrO2 positive electrode material to conduct an electrochemical potassium storage performance test in a full battery, and the specific steps are as follows:
[0056] The Sb / NC composite electrode sheet was prepared by using the above-mentioned effect example 2, and was pre-potassiumized in advance to improve the coulombic efficiency. 0.69 The preparation process of the CrO2 positive electrode material electrode sheet is as follows: the positive electrode active material, C45 and PVDF are mixed in N-methylpyrrolidone (NMP) solvent at a mass ratio of 8:1:1, and then evenly mixed using a homogenizer and coated on aluminum foil, dried in an oven at 120°C, and thoroughly dried in a vacuum oven after rolling and cutting. The diaphragm is glass fiber, the electrolyte is 5 mol / L KFSI dissolved in DME solvent, and the battery uses a 2025 button cell. The potassium storage performance test is carried out in the voltage range of 1.5 to 3.8V. The results are as follows Fig.10 As shown, it exhibits better cycle performance at a current density of 5 mA / g, which indicates that the Sb / NC composite material obtained in Example 1 also exhibits good electrochemical performance in a full battery, and is not limited to a potassium half-cell, and has practical significance for wide application.
[0057] Although the present invention has been disclosed as above in the preferred embodiment, it is not intended to limit the present invention. Anyone familiar with this technology can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention should be based on the definition of the claims.
Claims
1. A method for preparing antimony nitrogen carbon nanosheets, characterized in that: include: S1, dissolving furfural and antimony trichloride in N,N-dimethylformamide solvent, and stirring to obtain a reaction solution; S2, transferring the reaction solution to a reaction vessel for solvothermal reaction, and washing, centrifuging, and drying the product after the reaction to obtain a precursor; S3, placing the precursor in a tube furnace for carbonization treatment to obtain antimony nitrogen carbon nanosheets.
2. The method for preparing antimony nitrogen carbon nanosheets according to claim 1, characterized in that: The mass ratio of furfural to antimony trichloride in S1 is 2:(1-2).
3. The method for preparing antimony nitrogen carbon nanosheets according to claim 2, characterized in that: The mass ratio of furfural to antimony trichloride in S1 is 2:1.
17.
4. The method for preparing antimony nitrogen carbon nanosheets according to claim 1, characterized in that: The solvent thermal reaction temperature in S2 is 160-180°C, the time is 8-10 hours, and the heating and cooling time is 2-3 hours.
5. The method for preparing antimony nitrogen carbon nanosheets according to claim 1, characterized in that: The washing in S2 is three times of water washing and three times of anhydrous ethanol washing.
6. The method for preparing antimony nitrogen carbon nanosheets according to claim 1, characterized in that: In S2, the centrifugal speed is 6000-9000 rpm and the time is 1-5 minutes.
7. The method for preparing antimony nitrogen carbon nanosheets according to claim 1, characterized in that: The drying temperature in S2 is 60-80°C.
8. The method for preparing antimony nitrogen carbon nanosheets according to claim 1, characterized in that: In S3, the carbonization temperature is 350-400°C, the time is 1-2h, and the heating rate is 1°C / min.
9. An antimony nitrogen carbon nanosheet obtained by the preparation method according to any one of claims 1 to 8.
10. An application of the antimony nitrogen carbon nanosheet according to claim 9, characterized in that: Used as negative electrode material in potassium ion batteries.
Citation Information
Patent Citations
A method for preparing two-dimensional antimony nanosheets
CN113059174B
Metallic antimony / graphene composite material, and preparation method and application thereof
CN102760871A
Preparation method of antimony / nitrogen doped graphene compound, and obtained material and application thereof
CN108649191A